MEsenchymal StEm cells for Multiple Sclerosis (MESEMS): a randomized, double blind, cross-over phase I/II clinical trial with autologous mesenchymal stem cells for the therapy of multiple sclerosis - Uccelli, Antonio; Laroni, Alice; Brundin, Lou; Clanet, Michel; Fernandez, Oscar; Nabavi, Seyed M; Muraro, Paolo A; Oliveri, Roberto S; Radue, Ernst W; Sellner, Johann; Soelberg Sorensen, Per; Sormani, Maria P; et al. (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Multiple sclerosis (MS) is an inflammatory disease of the central nervous system with a degenerative component, leading to irreversible disability. Mesenchymal stem cells (MSC) have been shown to prevent inflammation and neurodegeneration in animal models of MS, but no large phase II clinical trials have yet assessed the exploratory efficacy of MSC for MS. Methods/design This is an academic, investigator-initiated, randomized, double-blind, placebo-compared phase I/II clinical trial with autologous, bone-marrow derived MSC in MS. Enrolled subjects will receive autologous MSC at either baseline or at week 24, through a cross-over design. Primary co-objectives are to test safety and efficacy of MSC treatment compared to placebo at 6 months. Secondary objectives will evaluate the efficacy of MSC at clinical and MRI levels. In order to overcome funding constraints, the MEsenchymal StEm cells for Multiple Sclerosis (MESEMS) study has been designed to merge partially independent clinical trials, following harmonized protocols and sharing some key centralized procedures, including data collection and analyses. Discussion Results will provide patients and the scientific community with data on the safety and efficacy of MSC for MS. The innovative approach utilized to obtain funds to support the MESEMS trial could represent a new model to circumvent limitation of funds encountered by academic trials. Trial registration Andalusia: NCT01745783 , registered on Dec 10, 2012. Badalona: NCT02035514 EudraCT, 2010–024081–21. Registered on 2012. Canada: ClinicalTrials.gov, NCT02239393 . Registered on September 12, 2014. Copenhagen: EudraCT, 2012–000518-13 . Registered on June 21, 2012. Italy: EudraCT, 2011–001295-19, and ClinicalTrials.gov, NCT01854957 . Retrospectively registered on May 16, 2013. London: Eudra CT 2012–002357-35, and ClinicalTrials.gov, NCT01606215 . Registered on May 25, 2012. Salzburg: EudraCT, 2015–000137-78 . Registered on September 15, 2015. Stockholm: ClinicalTrials.gov, NCT01730547 . Registered on November 21, 2012. Toulouse: ClinicalTrials.gov, NCT02403947 . Registered on March 31, 2015.